Uporabnost empirične fenomenologije na področju raziskovanja družine in medosebnih odnosov - Pate, Tanja (Bogoslovni vestnik, 2024)
Empirical phenomenology is an important method in the field of qualitative research, which aims to accurately describe an individual’s experience of phenomena. The paper discusses phenomenology in psychological research and its relevance in marriage and family therapy and research on interpersonal relationships and human experiences. The basic thesis of the paper is that the method presented provides a deep understanding of the subjective experiences of individuals in marriage and family therapy and sheds light on the complexity of interpersonal relationships and individual experiences. This contributes to a better understanding of human experience in the spiritual, psychological and social dimensions of life and to the development of more effective therapeutic interventions. Applications of the phenomenological method in psychotherapy,such as descriptive and interpretive phenomenological analysis, are highlighted, as well as implications for clinical practice.
Keywords: descriptive phenomenology; interpersonal relationships; interpretativna fenomenologija; interpretive phenomenology; kvalitativno raziskovanje; medosebni odnosi; opisna fenomenologija; qualitative research; subjective experience; subjektivna izkušnja